Barriers to accessing mental health services in Somali‐Australian women: a qualitative study. (14th March 2021) - Said, Mulki; Boardman, Gayelene; Kidd, Susan
Abstract: Despite the global prevalence of mental disorders being widely acknowledged, mental illness, complex trauma and the significant impact on individuals, families and communities continues to be poorly recognized, under‐diagnosed and underreported. Based on the 2017 Australian census, one‐in‐five (20%) people have experienced some type of mental illness within the last 12 months (Australian Bureau of Statistics [ABS], 2019). The prevalence rate of mental illness in culturally and linguistically diverse (CALD) communities is difficult to estimate due to cultural and linguistic issues and underutilization of mental health services. In particular, little epidemiological data is available about the prevalence of mental illness in the Somali‐Australian community. The aim of this study was to identify the perceived barriers to help‐seeking for mental health for Somali‐Australian women. A qualitative descriptive study incorporating focus group discussions with 31 Somali‐Australian women was conducted in Melbourne, Australia. Braun & Clarke's (2006) thematic analysis was applied to the data. Four themes relating to help‐seeking barriers were abstracted. Influence of faith explored how Islam can impact the person views on mental illness. Stigma focused on the relationship between public and self‐stigma and help‐seeking. Mistrust of Western healthcare system describes the participants concerns about the cultural disconnect between the community and the Western healthcare system. Finally, denial of mental illness reflected the community views on mental health. This study provides an insight into the factors that influence the Somali‐Australian community help‐seeking with mental health services. The findings have implications for mental health professionals and the Somali‐Australian community.